Loranthus (Taxillus vestitus) Infestation in Mixed Oak Forest Sites in and around Nainital Catchment of Central Himalayan Region - Gumber, Surabhi; Tewari, Ashish; Tewari, Beena (Indian Forester, 2017)
Mistletoes are a diverse group of parasitic plants with a worldwide distribution. The parasite Taxillus vestitus (Loranthus vestitus) causes wide spread infestation in the oak (Quercus) forest of the Central Himalaya located between 1740 and 2292 m. The study was undertaken across nine oak dominated sites in Nainital forest division of Kumaun Central Himalaya to assess the percent infestation and infestation intensity by this parasite on different forest tree species such as Quercus leucotrichophora (Q. incana), Q. floribunda (Q. dilatata), Q. lanata (Q. lanuginose) and Populus ciliata. Quercus floribunda had mean maximum infestation frequency (53.43Â±12.96) and infestation intensity (40.78Â±7.0). The older trees, which were severely lopped, had higher infection % branch-1 however, overall younger trees were more severely affected by the parasite. The coniferous trees species were not infected by the parasite across the study sites.